High Expression of Complement Component C7 Indicates Poor Prognosis of Breast Cancer and Is Insensitive to Taxane-Anthracycline Chemotherapy - Zhang, Huikun; Zhao, Yawen; Liu, Xiaoli; Fu, Li; Gu, Feng; Ma, Yongjie (Frontiers in Oncology, 2021)
Background: Breast cancer is the most commonly diagnosed cancer worldwide. However, the well-known biomarkers are not enough to meet the needs of precision medicine. Novel targets are desirable and highly valuable for improved patient survival. In this regard, we identified complement component C7 as one of the candidates based on data from OCOMINE database. Methods: C7 expression was examined by immunohistochemistry in 331 cases of invasive ductal carcinoma (IDC), 45 cases of ductal carcinoma in situ (DCIS) and 52 cases of non-neoplastic tissues adjacent to tumor. Then C7 expression was further confirmed by western blot analysis based on IDC specimens and non-neoplastic breast specimens. The relationship between C7 expression and breast cancer patients’ prognosis was analyzed in order to investigate the function of C7 in breast cancer patients. Meanwhile, we also analyzed the relationship between C7 expression and prognosis of 149 patients treated with conventional TE (taxane and anthracycline)-based chemotherapy. Then a cohort of patients (22 cases) treated with TE neoadjuvant chemotherapy was used to further confirm the relationship between C7 expression and TE-based chemosensitivity. Results: In our present study, we reported for the first time that C7 was an independent prognostic factor of breast cancer and C7 expression of IDC tissues was higher than non-neoplastic tissues adjacent to tumor and DCIS. In a cohort of 331 IDC patients, high expression of C7 indicated poor prognosis especially in triple negative subtype and luminal B subtype. Furthermore, C7 was also a promoting factor for triple negative subtype patients to develop bone metastasis. Meanwhile, we provided the first evidence that patients with high C7 expression were insensitive to TE (taxane and anthracycline)-based chemotherapy by analyzing a cohort of 149 patients treated with TE-based chemotherapy and another cohort of 22 patients treated with TE neoadjuvant chemotherapy. Conclusions: In summary, high expression of C7 may promote breast cancer development and might be insensitive to TE-based chemotherapy. Our present study laid a foundation to help clinicians improve identification of patients for TE-based chemotherapy by C7 in the era of precision medicine.